Hydration in hot weather: Tennis exercise drink recommendations - Robin, N.; Carien, R.; Dominique, L.; Ruart, S. (Coaching and Sport Science Review, 2022)
It is essential that tennis players have an appropriate, regular, and sufficient fluid intake. Indeed, athletes generally consume much less fluid than the losses induced by thermoregulatory mechanisms (mainly by sweating), caused by the combination of physical exercise and heat-related stress, when playing in hot condition.. This article aims to evoke the physiological and psychological mechanisms involved in the practice of tennis, training, or competition, in hot conditions (i.e., more than 25°C) dry or humid and to propose suggestions concerning the beverage use among tennis players. Applied recommendations, concerning pre- (before), per- (during) and post- (after) exercise hydration, are provided to anticipate and limit performance declines as well as prevent the risk of disorders, physiological conditions such as cramps, premature exhaustion, injuries and even heatstroke, as well as the psychological and motivational damage caused by dehydration.